MEASUREMENT OF CHANGES IN CHOROIDAL THICKNESS BY OPTICAL COHERENCE TOMOGRAPHY OF DIABETIC PATIENTS AFTER PAN-RETINAL PHOTOCOAGULATION - Ahmad, Imran; Rehman, Mubashir; Tariq Khan, Muhammad; Tahir, Mohammad Zeeshan; Khan, Jahanzaib (Journal of Postgraduate Medical Institute, 2019)
Objective: To find out changes in choroidal thickness by optical coherence tomography (OCT) of diabetic patients after pan-retinal photocoagulation (PRP). Methodology: This case series study was conducted at Hayatabad Medical Complex, Peshawar and Bacha Khan Medical Complex, Swabi from January 2015 to February 2018. One hundred patients with diabetic retinopathy (DR) undergoing PRP were selected by consecutive sampling. All patients underwent enhanced depth images of spectral domain OCT for choroidal thickness at baseline before PRP. After PRP, all patients were followed up after 4 and 12 weeks with repeated OCT to check for choroidal thickness. Results: A total of 146 eyes of 100 patients were included in the study. The mean age was 58.35 ±4.89. Mean baseline choroidal thickness on OCT for central 1mm zone was 312.92 ±23.73µ, for intermediate 3 mm it was 321.22 ±18.88µ while for outer 6 mm zone it was 329.11 ±27.22µ. After four weeks of PRP, mean choroidal thickness on OCT for central 1mm zone was 331.67 ±15.22µ, for intermediate 3 mm was 344.21 ±19.33µ while for outer 6 mm it was 349.99 ±21.56µ. At 12 weeks, mean OCT for central 1mm was 281.1 ±17.11µ, for intermediate 3 mm was 276.21 ±19.21µ while for outer 6 mm it was 269.49 ±21.34µ. Conclusion: There was transient increase in choroidal thickness after PRP. However, after 12 weeks there was gradual decline in choroidal thickness which was more than the initial pre-treated state.